The Volatile Constituents and Antimicrobial Analysis of Parietaria Officinalis from the Northern Part of Iran, Guilan Province: The volatile constituents analysis of Iranian Parietaria officinalis - Mahdavi Fikjvar, Edris; Golmohammadi, Shida; Jalali, Amir (Iranian Journal of Pharmaceutical Sciences, 2024)
The antimicrobial activity of the methanol extract of Parietaria officinalis from Guilan Province in northern Iran was evaluated against Escherichia coli (E. coli) (Gram-negative) and Staphylococcus aureus (S. aureus) (Gram-positive) using the microtitre plate method to determine the Minimum Inhibitory Concentration (MIC). The Folin-Ciocalteu method was used to analyze the total phenolic compounds. The amount of flavonoids present was determined using the colorimetric aluminum chloride technique. The essential oil of P. officinalis was analyzed to identify its primary components through chemical analysis. Gas Chromatography with a flame ionization detector (GC-FID) and Mass Spectrometry (MS) using a gas chromatograph (GC) (GC-MS) were utilized to analyze the components of the essential oil from wild-grown P. officinalis in Iran. The lowest concentration that inhibits growth for Staphylococcus aureus is 0.01 mg/µL, while for Escherichia coli is 5 mg/µL. The extract showed greater effectiveness against S. aureus than the gram-negative bacteria, E. coli. The total phenolic content was measured at 72.06 (SD=1.48), equivalent to micrograms of phenolic compounds in terms of gallic acid per milligram of dry methanolic extract. The total flavonoid content was recorded at 48.14 (SD=5.05), equivalent to micrograms of flavonoid compounds per milligram of dry methanolic extract. Among 65 observed compounds, 62 components were identified, constituting approximately 98.2%. The oil was rich in geranyl acetate (15.0 %), Viridiflorol (8.9%), trans-β-Ionone (4.8%), Caryophyllene oxide (4.7%), Hexahydrofarnesyl acetone (4.2%), 2,3-Epoxygeranial (4.2%), Bornyl angelate (2.3%) and (-)-Spathulenol (2.2 %). This research found that P. officinalis could be a promising natural substitute for antibiotics in treating S. aureus infections. The antibacterial effects are likely due to its phytochemical components. Results indicated that the P. methanolic extract possessed significant potential for both flavonoid and phenolic content. The extract obtained by the proposed procedure is enriched with flavonoids and is a candidate for a wide range of pharmacological properties.